Diseño de una guía para la aplicación y tratamiento de las últimas reformas tributarias contempladas en el código de la producción con respecto a los incentivos tributarios - Vinueza Pacheco, María Belén (2013)
This thesis summarizes the processes, in a guide to follow to implement tax incentives considered in the “Código Orgánico de la Producción, Comercio e Inversiones”. The code is a regulatory tool for all the productive activities generated in the country, besides, this code reforms existing laws in the business, this as a tool of the government to take direct approach to the productive sector. Incentive major groups considered in this presentation are: General incentives, which are applicable in any type of investment in the country.